Spatial disorientation and executive dysfunction in elderly nondemented patients with Parkinson’s disease - Cammisuli, Davide M (Neuropsychiatr Dis Treat, 2018)
OBJECTIVES: Patients with Parkinson’s disease (PD) present with a wide range of cognitive deficits. Cognitive impairment is recognized as an independent nonmotor aspect of the disorder and has a critical role in functional outcome and conversion into PD dementia. To date, everyday memory impairment in elderly patients with PD is underinvestigated and its relationship with executive dysfunction was not clearly explained. Our study aims at clarifying the neuropsychological pattern of everyday memory and executive deterioration in elderly patients with PD. METHODS: Forty nondemented PD patients (mean age 71.2 years; M:F = 29:11) and 30 well-matched controls (mean age 70.7 years; M:F = 15:15) were assessed on everyday memory (Rivermead Behavioral Memory Test [RBMT]) and executive functioning (Frontal Assessment Battery [FAB]) measures. Mann–Whitney U-tests (Bonferroni corrected) were used to compare groups on these measures and Spearman’s rank correlations were performed to highlight their associations. RESULTS: PD patients performed worse than controls on recall for novel tasks and geographic recall (RMBT) as well as lexical fluency and mental flexibility (FAB). Particularly, spatial orientation depending on egocentric navigation seems to be altered in PD patients. The clinical group showed poorer performances than controls in mental flexibility, sensitivity to interference, and inhibitory control. Such measures were associated with immediate and delayed recall, picture recognition, prospective memory, and orientation tasks of everyday memory. CONCLUSION: Executive-type difficulties and memory-type difficulties have an impact on cognitive performances of elderly patients with PD. We recommend using the RBMT and the FAB as part of routinely neuropsychological battery for assessing PD patients.